Does Provider Self‐Reporting of Etiquette Behaviors Improve Patient Experience? A Randomized Controlled Trial. Issue 6 (1st June 2017) - Siddiqui, Zishan; Qayyum, Rehan; Bertram, Amanda; Durkin, Nowella; Kebede, Sosena; Ponor, Lucia; Oduyebo, Ibironke; Allen, Lisa; Brotman, Daniel J.
Abstract : BACKGROUND: There is a glaring lack of published evidence‐based strategies to improve the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) patient experience scores on the physician domain. Strategies that have been used are resource intensive and difficult to sustain. OBJECTIVE: We hypothesized that prompting providers to assess their own etiquette‐based practices every 2 weeks over the course of 1 year would improve patient experience on the physician domain. DESIGN: Randomized controlled trial. SETTING: 4 acute care hospitals. PARTICIPANTS: Hospitalists. INTERVENTION: Hospitalists were randomized to the study or the control arm. The study arm was prompted every 2 weeks for 12 months to report how frequently they engaged in 7 best‐practice bedside etiquette behaviors. Control arm participants received similarly worded questions on quality improvement behaviors. MEASUREMENT: Provider experience scores were calculated from the physician HCAHPS and Press Ganey survey provider items. RESULTS: Physicians reported high rates of etiquette‐based behavior at baseline, and this changed modestly over the study period. Self‐reported etiquette behaviors were not associated with experience scores. The difference in difference analysis of the baseline and postintervention physician experience scores between the intervention arm and the control arm was not statistically significant ( P = 0.71). CONCLUSION: In this 12‐month study, biweekly reflection and reporting of best‐practice bedside etiquette behaviors did not result in significant improvement on physician domain experience scores. It is likely that hospitalists' self‐assessment of their bedside etiquette may not reflect patient perception of these behaviors. Furthermore, hospitalists may be resistant to improvement in this area since they rate themselves highly at baseline.